Imperial appropriations - the dynamic history of iziqu - Guy, J. (Southern African Humanities, 2016)
Iziqu are carved, interlocking beads conventionally supposed to have been awarded to soldiers in the Zulu army for valour. This paper demonstrates the variety of meanings which have attached themselves to these beads, as they have interacted with the changing forces and dynamics of the social history of KwaZulu-Natal over the past one hundred and eighty years.